Presa in carico infermieristica nella Malattia Renale Cronica - Maria Pia Zito; Roberta Toschi (AboutScience Srl, 2021)
n 2017, thanks to an initiative of IPASVI College (the Order of Nursing Professionals of the province of Bologna) in response to 2014 legislations referring to the Guidelines about Chronic Kidney Disease (CKD), nephrology professionals and members of EDTNA/ERCA Italian Branch Association (which in 2018 became Società Infermieri Area Nefrologica, SIAN) in 2021 were requested to contribute to define the role and skills performed by nurses on a daily basis. The management of the CKD patient has been structured into 7 phases: the model for each phase takes into consideration the professionals involved, the care settings and the tools used. To support this approach, we decided to introduce two elements which broaden the clinical and care approach to the patient and at the same time highlight the contribution of nursing professionals, with a referring workflow for the CKD patient, the nurses' role and skills required throughout the patient's journey. Furthermore, to ensure the best continuity of care, we believe that it is necessary to apply a logical model based on the principles of early recognition of health and welfare needs; guarantee the most appropriate healthcare response; ensure early care; standardize the procedures of professionals to improve the quality of life of the patient and manage the social and economic impact.